Forecasting the impact of buildings with multi-storey underground parts on the displacement of subsoil using modern numerical tools - Michalak, Hanna; Przybysz, Paweł (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
Różański, Adrian. Redakcja
Poprzedni tytuł: Studia Geotechnica
Studia Geotechnica et Mechanica, Vol. 43, 2021, s1, s. 479-491
Keywords: geotechnika; mechanika; buildings with multi-storey undergrounds; deep building foundations; 3D numerical modelling; soil displacement; influence on neighbouring constructions